Soteriologi dalam Sakramen Protestan: Tinjauan Dogmatis HKBP terhadap Keselamatan - Tambun, Roy Haries Ifraldo (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2024)
Salvation is a divine grace bestowed by God upon humanity through the sacrifice of His Son. Within Protestant doctrine, this salvation exclusively emanates from Jesus Christ. No individual possesses the ability to grant salvation to their fellow human beings. Through a qualitative research approach, the researcher conducts an examination of the concept of salvation to obtain a deeper and more comprehensive understanding. This study focuses on analyzing the concept of salvation within the context of two holy sacraments implemented in Protestant teachings. Based on the literature review derived from books and scholarly journals, this research concludes that salvation can only be obtained through Christ. Each individual who has received this gift of salvation is expected to actualize it in their daily lives as a manifestation of their identity as beings who have known and been saved by Jesus Christ. AbstrakKeselamatan merupakan anugerah yang diberikan Allah kepada umat manusia melalui pengorbanan Putra-Nya. Dalam doktrin Protestan, keselamatan tersebut hanya bersumber dari Yesus Kristus. Tidak seorangpun memiliki kemampuan untuk memberikan keselamatan kepada sesamanya. Melalui pendekatan penelitian kualitatif, peneliti melakukan pengkajian terhadap konsep keselamatan untuk memperoleh pemahaman yang lebih mendalam dan komprehensif. Penelitian ini menitikberatkan pada analisis konsep keselamatan dalam konteks dua sakramen kudus yang diimplementasikan dalam ajaran Protestan. Berdasarkan hasil telaah literatur yang bersumber dari referensi buku dan jurnal ilmiah, penelitian ini menyimpulkan bahwa keselamatan hanya dapat diperoleh melalui Kristus. Setiap individu yang telah menerima anugerah keselamatan tersebut diharapkan dapat mengaktualisasikannya dalam kehidupan sehari-hari sebagai manifestasi dari identitasnya selaku insan yang telah mengenal dan diselamatkan oleh Yesus Kristus.